Cone Photoreceptor Degeneration and Neuroinflammation in the Zebrafish Bardet-Biedl Syndrome 2 (bbs2) Mutant Does Not Lead to Retinal Regeneration - Song, Ping; Fogerty, Joseph; Cianciolo, Lauren T.; Stupay, Rachel; Perkins, Brian D. (Frontiers in Cell and Developmental Biology, 2020)
Bardet-Biedl syndrome (BBS) is a heterogeneous and pleiotropic autosomal recessive disorder characterized by obesity, retinal degeneration, polydactyly, renal dysfunction, and mental retardation. BBS results from defects in primary and sensory cilia. Mutations in 21 genes have been linked to BBS and proteins encoded by 8 of these genes form a multiprotein complex termed the BBSome. Mutations in BBS2, a component of the BBSome, result in BBS as well as non-syndromic retinal degeneration in humans and rod degeneration in mice, but the role of BBS2 in cone photoreceptor survival is not clear. We used zebrafish bbs2-/- mutants to better understand how loss of bbs2 leads to photoreceptor degeneration. Zebrafish bbs2-/- mutants exhibited impaired visual function as larvae and adult zebrafish underwent progressive cone photoreceptor degeneration. Cone degeneration was accompanied by increased numbers of activated microglia, indicating an inflammatory response. Zebrafish exhibit a robust ability to regenerate lost photoreceptors following retinal damage, yet cone degeneration and inflammation was insufficient to trigger robust Müller cell proliferation. In contrast, high intensity light damage stimulated Müller cell proliferation and photoreceptor regeneration in both wild-type and bbs2-/- mutants, although the bbs2-/- mutants could only restore cones to pre-damaged densities. In summary, these findings suggest that cone degeneration leads to an inflammatory response in the retina and that BBS2 is necessary for cone survival. The zebrafish bbs2 mutant also represents an ideal model to identify mechanisms that will enhance retinal regeneration in degenerating diseases.